A imaginação na série “Divertimento com sinais ortográficos”, de Alexandre O’Neill - Bueno, Danilo (eLyra, 2021)
This article discusses Alexandre O’Neill’s poetry series “Divertimento com sinais ortográficos”, analyzing the poetics of its graphic signs, and more specifically, how they both create visual poetry, and reflect surrealism’s focus on the imagination.